«Coronavirus» como manchachi. Notas acerca de las concepciones y conductas ante el miedo - Mujica Bermúdez, Luis (2020)
The article analyzes the meaning of the manchasqa term or mancharisqa (scared), at the time of the coronavirus or SARS-CoV-2, among the people in Andes Quechua, and behaviors that take the threat of the spread of the virus in the context of emergency arranged by the Peruvian Government. The concept of ‘scare’ is reviewed, drawing on the mythical Quechua tradition, the medical tradition, the social sciences and the human sciences, such as psychology and philosophy. A typology is proposed, as a hypothesis, of the ways of understanding mancharisqa (being scared) in an area of the Andes.